Female‐directed aggression by adolescent male chimpanzees primarily constitutes dominance striving, not sexual coercion. Issue 1 (3rd May 2021) - Enigk, Drew K.; Emery Thompson, Melissa; Machanda, Zarin P.; Wrangham, Richard W.; Muller, Martin N.
Abstract: Objectives: Chimpanzees ( Pan troglodytes ) are notable for exhibiting high levels of male‐to‐female aggression. Much of this aggression from adult males serves sexually coercive functions. Despite being smaller and lower‐ranking than adult males, adolescent males also engage in regular aggression against adult females. Here, we test whether the primary function of this aggression is sexual coercion, as in adult males, or, alternatively, whether adolescent males use aggression to establish social dominance over females. Materials and Methods: We analyzed 1771 copulations and 1812 instances of male‐initiated aggression between adolescent males (aged nine through 14 years) and adult females across 21 years of observation of the Kanyawara chimpanzee community in Kibale National Park, Uganda. Results: Our test of the sexual coercion hypothesis revealed that adolescent males did not selectively target cycling females for aggression, nor did aggression against cycling females predict rates of copulation with those females. Our test of the social dominance hypothesis showed that males succeeded in dominating all adult females before, or soon after, dominating their first adult male. Additionally, we found that adolescent males dominated females approximately in the order of the females' own ranks, from the bottom to the top of the female hierarchy. Discussion: Our data illustrate that the establishment of social dominance was more important than sexual coercion in explaining patterns of adolescent male aggression toward females. In comparison, evidence for sexual coercion was clear and compelling in adult males. These findings highlight that the primary function of male‐to‐female aggression differs between adolescent and adult males. Abstract : Adolescent males dominated low‐ranking females before high‐ranking females.